Substantial Increases in Chlamydia and Gonorrhea Positivity Unexplained by Changes in Individual-Level Sexual Behaviors Among Men Who Have Sex With Men in an Australian Sexual Health Service From 2007 to 2013. Issue 2 (February 2015) - Chow, Eric P.F.; Tomnay, Jane; Fehler, Glenda; Whiley, David; Read, Tim R.H.; Denham, Ian; Bradshaw, Catriona S.; Chen, Marcus Y.; Fairley, Christopher K.
<x xml:space="preserve">Abstract</x> Background To determine the risk-adjusted temporal trend of gonorrhea and chlamydia positivity and associated risk behaviors among men who have sex with men (MSM) attending a sexual health clinic in Melbourne in Australia. Methods Gonorrhea and chlamydia positivity by anatomical site adjusted for year of test, age, number of sexual partners, and condom use among MSM attending Melbourne Sexual Health Centre from 2007 to 2013 were calculated using generalized estimating equation regression models. Results A total of 12, 873 MSM were included with a median age of 30.0 years. The proportion with pharyngeal, urethral, and anal gonorrhea was 1.7%, 2.3%, and 2.9%, respectively. The adjusted odds of gonorrhea positivity increased by 9% (95% confidence interval [CI], 3%–15%), 11% (95% CI, 6%–17%), and 12% (95% CI, 7%–17%) per year, respectively. The proportion of MSM who were infected with anal chlamydia was 5.6%, with an average increase of 6% (95% CI, 3%–10%) per year; however, no significant change was observed in urethral chlamydia positivity (adjusted odds ratio, 1.02; 95% CI, 0.98–1.06). Increases in gonorrhea and chlamydia positivity were primarily restricted to MSM who reported more than 10 partners in 12 months. The number of partners in the last 12 months fell from 16.6 to 10.5, whereas consistent condom use with casual partners decreased from 64.6% to 58.9% over the study period. Conclusions Gonorrhea and chlamydia have increased among MSM despite the decrease in the number of sexual partners and are occurring primarily in MSM with high numbers of partners and persist after adjusting for known risk factors, suggesting that unmeasured factors (e.g., more assortative mixing patterns) may explain the observed changes.